Sampled-data controllability and stabilizability of Boolean control networks: Nonuniform sampling. Issue 12 (August 2018) - Yu, Yongyuan; Feng, Jun-e; Wang, Biao; Wang, Peihe
Abstract: Derived from a simplified intelligent traffic control system, sampled-data controllability and stabilizability of Boolean control networks are considered. Compared with the existing case of uniform (periodic) sampling in Boolean control networks, the nonuniform one is more general. Using linear span with integral coefficients, the distribution of sampling points can be obtained. Then by constructing novel systems, some necessary and sufficient conditions are proposed to determine sampled-data controllability and stabilizability. Finally, two illustrative examples, which are on apoptosis networks and traffic control systems, respectively, are worked out to show the effectiveness of the obtained results.